Factors of in-App Purchase Intention for Smartphones Among Saudi: Theoretical Extension and Analysis - Barq, Abbas Al; Falah, Khalid Al (Journal of Posthumanism, 2025)
The expansion of the smartphone market and the advancement of its applications (apps) has transformed the economy of mobile apps. However, despite this, many mobile apps fail to attract customers, yet there has been a lack of research and understanding of the factors that affect the decisions to buy them. Accordingly, in emerging nations like Saudi Arabia, there are scant studies to determine and understand the primary determinants that can affect the decision of users to buy paid mobile apps. Therefore, this research aims to explore the key determinants that consumers contemplate while making purchasing decisions for mobile apps for their smart devices. This study adopted a descriptive-analytical technique and data was gathered by administrating an electronic questionnaire survey. A total of 1000 participants was targeted through convenient sampling, of which only 614 questionnaires with complete information were returned. Structural equation modeling (SEM) was employed to conduct the hypothesis testing of the questionnaire. The findings highlight that all determinants are important when deciding to purchase a paid mobile app. These determinants incorporate app trialability, Price value of the app, app usefulness, Electronic Word-of-Mouth about the app (eWOM), app technical reliability, app performance, and app enjoyment. This study provides valuable insights regarding the decisive factors of users to purchase paid mobile apps. It also helps marketers and developers in revenue generation by improving their sales of apps.